Static-light hadrons on a dynamical anisotropic lattice - PEARDON, MICHAEL JAMES; RYAN, SINEAD MARIE; SKULLERUD, JONIVAR (Proceedings of Science, 2005)
We present preliminary results for the static-light meson and baryon spectra for Nf = 2 QCD. The study is performed on an anisotropic lattice and uses a new all-to-all propagator method allowing us to determine particle masses to a high precision.
PUBLISHED
Keywords: Pure & Applied Mathematics